Overcoming Creative Block and Generating Innovative Ideas for Development: Heuristics for Art/Design - Ebigbagha Zifegha Sylvester (New Horizons in Education and Social Studies Vol. 8, 2021)
Ideas and concepts generation are the nucleus of innovation, growth and development of material culture. Nevertheless, creative professionals, often get stuck or bereft of ideas during product development process (not resulting from physical, physiological, or psychological disturbances but from prevalence unawareness of strategies for creating ideas). This is a problem that paralyzes creative efforts with grave consequences for the artist/designer in particular, and development in general. Therefore, as a panacea, this paper focused on heuristics for generating innovative ideas for development with particular emphasis on art/design. Towards this end, a triangulation of methods: critical-historical-analytic examination, artistic exploration, and content analysis are employed. The paper introduced the reader to the need for strategies to generate innovative ideas, stimulate creative thinking, and foster intrinsic motivation that enhance creativity. Furthermore, it highlighted the multi-faceted process of material culture production that involves creativity, knowledge production/ utilization, and form generation. Also, the paper discussed heuristics for new ideas in material culture development, which include brainstorming, design questioning, Six honest serving men, Pentad, and Tagmemics/Shifting perspectives. These are found to be pivotal for success in creating ideas for form- generation in art/design. The paper ended with the need for artists/designers to be conversant with, internalize, and utilize these heuristics to optimally generate creative ideas for product development with satisfactory outcomes.